2016
DOI: 10.1016/j.ijscr.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic disease, panniculitis, polyarthrtitis syndrome successfully treated with total pancreatectomy: Case report and literature review

Abstract: HighlightsPPP (pancreatic disease, panniculitis, polyarthritis) syndrome is a rare disease caused by pancreatitis or pancreatic cancer.Panniculitis and polyarthritis are the main characteristics of the syndrome.A high mortality rate and chronic sequel are reported.Surgical and endoscopic treatment may improve the prognosis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
2
17
0
11
Order By: Relevance
“…Since this report, there have been few documentations of the condition and this may be due to misleading signs and symptoms that lead diagnosis of the condition and therefore incidence could be greatly under-reported. A review of the published cases reveals that, similarly to the patient we have reported, the majority of patients do not present with abdominal pain,5 and up to 40% of patients may present with panniculitis or arthritis 6. This may be due to a large number of cases of PPP syndrome being secondary to malignancy.…”
Section: Discussionsupporting
confidence: 64%
“…Since this report, there have been few documentations of the condition and this may be due to misleading signs and symptoms that lead diagnosis of the condition and therefore incidence could be greatly under-reported. A review of the published cases reveals that, similarly to the patient we have reported, the majority of patients do not present with abdominal pain,5 and up to 40% of patients may present with panniculitis or arthritis 6. This may be due to a large number of cases of PPP syndrome being secondary to malignancy.…”
Section: Discussionsupporting
confidence: 64%
“…In the case of pancreatic cancer, surgery was recommended and endoscopic procedures such as pancreatic stenting have also been described. Steroids, non-steroidal anti-inflammatory drugs and immunosuppressants for skin lesions or arthritis have been found to be ineffective [15]. In the case presented in this report, the patient refused the mass resection and chemotherapy for treatment of pancreatic NET.…”
Section: Discussionmentioning
confidence: 81%
“…Thus DISCUSSION pancreatic pathology is typically the last of the triad to be detected. 8 The delay in diagnosing the etiology of the debilitating arthralgias in our patient is due to PPP syndromes' rarity and his disordered presentation. To our knowledge, our patient is the first case in which cutaneous manifestations appeared months later than the other components of the syndrome.…”
mentioning
confidence: 75%
“…6 Management of PPP syndrome is frequently aimed at treating the underlying pancreatic disease. 8 Panniculitis typically resolves following the resolution of the acute inflammation of the pancreatic parenchyma. Thus, supportive treatment, such as fluids and pain control, is all that is required.…”
mentioning
confidence: 99%